Comparison of the effects of three different dehorning techniques on behavior and performance in feeder cattle in a western Kansas feedlot - C.D. Neely; C.A. Kerr; David E. Anderson; Daniel U. Thomson; Christopher D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2012)
Removing the horns of cattle when they arrive at feeding facilities is a common practice to reduce injury to other cattle. Bruising on carcasses of cattle that have been housed in pens containing horned cattle increases noticeably. Horned feeder cattle marketed in Arkansas regional livestock auction barns received average discounts of 3.23/cwt in 2005, giving producers the incentive to dehorn their cattle before marketing. Three common techniques (tipping, dehorning, and banding) are utilized in the field to remove or reduce horn length in beef cattle. Tipping is the practice of removing the tip of the horn such that the diameter of the horn is approximately 1 to 1.5 inches in diameter. Dehorning is mechanically cutting the horns off at the base of the horn near the head. The use of high-tension rubber bands to dehorn cattle has recently been implemented in some cattle feeding facilities. The band restricts blood circulation to the horns, resulting in necrosis, and the horns eventually fall off. This study was conducted to establish baseline data on behavior and feedlot performance in cattle dehorned using these techniques.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; Dehorning; Performance; Feedlot